Dynamics of Centromeres during Metaphase–Anaphase Transition in Fission Yeast: Dis1 Is Implicated in Force Balance in Metaphase Bipolar Spindle - Nabeshima, Kentaro (The American Society for Cell Biology, 1998)
In higher eukaryotic cells, the spindle forms along with chromosome condensation in mitotic prophase. In metaphase, chromosomes are aligned on the spindle with sister kinetochores facing toward the opposite poles. In anaphase A, sister chromatids separate from each other without spindle extension, whereas spindle elongation takes place during anaphase B. We have critically examined whether such mitotic stages also occur in a lower eukaryote, Schizosaccharomyces pombe. Using the green fluorescent protein tagging technique, early mitotic to late anaphase events were observed in living fission yeast cells. S. pombe has three phases in spindle dynamics, spindle formation (phase 1), constant spindle length (phase 2), and spindle extension (phase 3). Sister centromere separation (anaphase A) rapidly occurred at the end of phase 2. The centromere showed dynamic movements throughout phase 2 as it moved back and forth and was transiently split in two before its separation, suggesting that the centromere was positioned in a bioriented manner toward the poles at metaphase. Microtubule-associating Dis1 was required for the occurrence of constant spindle length and centromere movement in phase 2. Normal transition from phase 2 to 3 needed DNA topoisomerase II and Cut1 but not Cut14. The duration of each phase was highly dependent on temperature.